THE ROLE OF THE PRINCIPAL IN OPTIMIZING THE TEACHER PERFORMANCE MANAGEMENT INFORMATION SYSTEM - Abdul Wahid Aminullah, Moh. Rofiki (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This study aims to analyze the role of the principal in managing and improving the quality of teacher performance in the field of education. The optimization of the teacher performance management information system is a strategic step to ensure the achievement of educational goals. At MAN 01 Bondowoso, the principal holds a key role in utilizing information technology to monitor, evaluate, and enhance teacher performance, thereby creating a more effective and high-quality learning process. This research employed a qualitative approach to understand the phenomena experienced by research subjects, such as behavior, perception, motivation, actions, and others, holistically and descriptively using words and language, within a specific and natural context through the use of various naturalistic methods. To ensure the accuracy and accountability of the data, information was collected through observation, interviews, and documentation. The data were analyzed using descriptive analysis. The data obtained from the field needed to be carefully and thoroughly recorded; therefore, data analysis was conducted immediately using the Miles and Huberman model, which includes data reduction, data display, and data verification. Triangulation of sources, techniques, and timing was implemented to ensure the study's transferability, dependability, and confirmability.The practical implication of these findings is the importance of digital leadership training for school principals and the integration of information technology into sustainable education management systems. The optimization of MIS directly contributes to improving teacher professionalism and the overall quality of education in madrasahs.